Herb Polysaccharide-Based Drug Delivery System: Fabrication, Properties, and Applications for Immunotherapy - Yubiao Cao; Zhuowen Chen; Liangliang Sun; Yameng Lin; Ye Yang; Xiuming Cui; Chengxiao Wang (MDPI AG, 2022)
Herb polysaccharides (HPS) have been studied extensively for their healthcare applications. Though the toxicity was not fully clarified, HPS were widely accepted for their biodegradability and biocompatibility. In addition, as carbohydrate polymers with a unique chemical composition, molecular weight, and functional group profile, HPS can be conjugated, cross-linked, and functionally modified. Thus, they are great candidates for the fabrication of drug delivery systems (DDS). HPS-based DDS (HPS-DDS) can bypass phagocytosis by the reticuloendothelial system, prevent the degradation of biomolecules, and increase the bioavailability of small molecules, thus exerting therapeutic effects. In this review, we focus on the application of HPS as components of immunoregulatory DDS. We summarize the principles governing the fabrication of HPS-DDS, including nanoparticles, micelles, liposomes, microemulsions, hydrogels, and microneedles. In addition, we discuss the role of HPS in DDS for immunotherapy. This comprehensive review provides valuable insights that could guide the design of effective HPS-DDS.